Le réseau des agglomérations antiques dans les cités du Massif central (ier s. av. J.-C.-ve s. apr. J.-C.) - Florian Baret (Gallia)
Long remained on the sidelines of research on the small towns, the ancient cities of the Massif Central have recently received a new analysis, conducted as part of a doctoral thesis. Thus, from a critical reading of the corpus of settlements obtained from the bibliographies, research conducted recently showed the diversity of cohousing medium mountain. In light of this work, it is possible to propose a classification of small towns and analyse their geography in the study areas. It shows a significant diffusion of the urban phenomenon, the distribution seems less influenced by the relief as communication channels which are however themselves very constrained by the topography. The chronological development of the urban framework shows a drop in enrollment began in the late 2th century but by no means a complete disappearance of the sites. However, this observation is greatly influenced by an incomplete documentation that remains largely silent for the 4th and 5th centuries is not to precisely characterise occupations. Finally, thematic analyses show contrasting settlements between highly urbanised sites and grouped habitats reduced to much simpler forms.